Numerical simulation on structure effects for linked cylindrical and spherical vessels. (September 2018) - Yan, C; Wang, ZR; Jiao, F; Ma, C
This paper presents a simulation study on the methane–air mixture explosions through using the eddy-dissipation concept (EDC) model in FLUENT. The aims are to investigate the structure effects of methane–air mixture explosions in a spherical vessel, cylindrical vessel and different systems of cylindrical vessels connected with pipe. Meanwhile, in order to study the characteristics of methane-air mixture explosions in the linked vessels, changes of flame temperature and airflow velocity in the linked vessels are simulated and analyzed. The results suggest that the effect of structural changes of a single vessel on the gas explosion intensity is clear, and the explosion intensity of a spherical vessel is greater than that of a cylindrical vessel. The simulation results of different structural forms of a cylindrical vessel connected with pipelines show that the time to reach the peak value of explosion pressure is the shortest in the linked vessels, and the explosion pressure rising rate is highest at the vessel's center. For the linked vessels, after ignition, the airflow ahead of the flame propagates to the secondary vessel, and the maximum airflow velocity of every monitoring point in the linked vessels increases. The detonation occurs when the flame propagates to the secondary vessel, which leads to a severe secondary explosion in the secondary vessel. The studies can provide an important reference for the safe design of industrial vessels.